A study of managing resistance that occurred in construction project - Noorfatin Liyana, Suhaimy (2014)
This research was conducted to identify the effective strategy used in managing resistance during project implementation for construction project from the perspective of project manager and project team. Besides that, the objective for this research was to rank the most effective strategy used in managing resistance during project implementation in order to help project manager and project team to be prepared with contingency plan and strategy because every project exposed with the unpredictable things. In this research, the method used for obtaining survey research was questionnaire for collecting the response from the project managers and project team. The Total respondents for this research were 19 from housing developer company that categorized in G2 and located in Negeri Sembilan. Next, Statistical Package for the Social Sciences (SPSS) was used in analyzing these research findings. The result for this research showed that communication plan was the most effective strategy used in managing resistance during project implementation with the highest value of mean. Last but not least, the main suggested recommendation for future research is to study the large number of respondents or participants by include project team from different categories of contractors for more accurate outcome and represent a more realistic population in Malaysia